Algorithm for turning detection and analysis validated under home-like conditions in patients with Parkinson’s disease and older adults using a 6 degree-of-freedom inertial measurement unit at the lower back - Pham, Minh H. (2022)
Copyright: © 2017 Pham, Elshehabi, Haertner, Heger, Hobert, Faber, Salkovic, Ferreira, Berg, Sanchez-Ferro, van Dieën and Maetzler. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY). The use, distribution or reproduction in other forums is permitted, provided the original author(s) or licensor are credited and that the original publication in this journal is cited, in accordance with accepted academic practice. No use, distribution or reproduction is permitted which does not comply with these terms.